Development of biocomposite filament for fused filament fabrication from soy hulls and soy protein isolate. (March 2023) - Dey, Arup; Rahman, Md Mahbubur; Yodo, Nita; Grewell, David
Abstract: The applications of the fused filament fabrication (FFF) process are limited due to the low variety of available materials and poor mechanical, thermal, and viscoelastic properties. Acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) are the two most widely used filament materials for the FFF process. Along with pure thermoplastics, different composite filament materials are also used for the FFF process to a limited extent. Exploring new materials for the FFF filaments is essential to obtain a wide range of material properties for different application requirements. In this paper, biobased and biodegradable composite filament materials are developed using PLA as a matrix and soy hulls and soy protein isolate (SPI) as fillers. Different proportions of soy hulls are blended with PLA, and the printability for the FFF process is also analyzed for the developed biocomposite filaments. The proportions of soy hulls analyzed are 5 wt%, 7.5 wt%, and 10 wt% for the FFF filament. The impacts of soy hulls ratios on tensile strength, melt flow index (MFI), glass transition temperature, and storage modulus are investigated using experimental analysis and statistical techniques. According to experimental results, 5 wt% soy hulls are preferable among the three proportions. Besides, 2.5 wt% SPI and 7.5 wt% soy hulls are blended with PLA to investigate the impacts of two fillers on these four properties. In this research, FFF filaments are successfully fabricated from soy hulls and SPI-based biocomposites. This study provided evidence that printing parts from PLA, soy hulls, and SPI blended biocomposites is possible. Graphical Abstract: ga1